PENGARUH TEORI MOTIVASI DUA FAKTOR TERHADAP KEPUASAN KERJA KARYAWAN - David Fernando Purba; Freddy Rangkuti (Jurnal Ilmiah Hospitality, 2022)
Job satisfaction is an element that is recognized as very important for a company or organization. Someone wants to work because of the emergence of an impulse from within him to get better expectations than before and certainly more satisfying. Frederick Herzberg states that a person when doing his job is influenced by two dominant factors including the Hygiene Factor and the Motivation Factor. Hygiene Factors are maintenance factors related to human nature so that bodily peace is obtained. Motivation Factors are factors related to individual psychological needs such as feeling perfect in doing work. The research method used is judgment sampling by collecting data through questionnaires distributed to 141 respondents who work at the Perkumpulan Strada school, North East Jakarta branch. The measuring instrument in this research is validity test, reliability test, percentage, average, Likert scale, structural equation model. Based on the results of the research, the analysis of the structural equation model shows that there is a significant positive influence of motivator factors on employee job satisfaction. There is a significant positive effect of hygiene factor on employee job satisfaction. There is a positive and significant relationship between motivator factors and hygiene factors.